“Beyond Specialization: The Role of General Education Programs in UAE Higher Education, Comparative Insights from Applied and Non-Applied Systems” - Al-Bukhari, Hala Abdullah; Khaled, Sobhi; Sarhan, Omar; Saali, Tariq (Journal of Cultural Analysis and Social Change, 2026)
The research aimed to investigate the role of general education programs in UAE higher education. It adopted the positive realism philosophy. A questionnaire was utilized to collect data from a sample of students and faculty members at applied and non-applied universities in the UAE. The population consisted of all members, undergraduate and postgraduate students, in the UAE. Furthermore, a simple random sample of 360 individuals from the population was taken. The study results demonstrated that the reality of implementing General Education Programs in the UAE Higher Education was at a high degree, reflecting the commitment of UAE universities to the Commission for Academic Accreditation Standards (CAA), which emphasizes the importance of including general education courses within all academic programs. In addition, the results revealed that the level of learning outcomes of general education programs in the UAE higher education reached a high level, indicating that the programs effectively achieved their educational and pedagogical goals. There were no statistically significant differences at a 0.05 level between the sample individuals’ mean degree concerning the role of the general education program in higher education, attributable to the gender variable. In comparison, there were statistically significant differences at the level of 0.05 between the mean degree of the sample individuals regarding the role of the general education program in higher education, due to the type of institution variable in favor of applied systems. The results also revealed that the general education program had a statistically significant impact on the program learning outcomes. The researcher recommended designing general education courses that focus on skills applicable to the local, regional, and international labor market demands.